Susceptibility towards Chickenpox, Measles and Rubella among Healthcare Workers at a Teaching Hospital in Rome - Giuseppe La Torre; Mattia Marte; Valentin Imeshtari; Corrado Colaprico; Eleonora Ricci; David Shaholli; Vanessa India Barletta; Pasquale Serruto; Aurelia Gaeta; Guido Antonelli (Vaccines, 2022)
Immunization is the best protection against chickenpox, measles and rubella. It is important to identify and immunize susceptible healthcare workers to prevent and control hospital infections. Our aim was to estimate the susceptibility level of healthcare workers at a Teaching Hospital in Rome concerning these diseases and the factors associated to the susceptibility. Methods: a cross sectional study was carried out at the Department of Occupational Medicine of the Umberto I General Hospital of Rome. Participants were recruited during routine occupational health surveillance. As far as inclusion criteria, the following professionals were considered: doctors, nurses, laboratory technicians and other health professionals. Concerning the exclusion criteria, patients with HIV, cancer and diseases of the immune system, and acute illness or fever more than 38.5 °C, were not included in the study. A blood sample was tested for the presence of antibodies against measles, rubella and chicken pox. Results: 1106 healthcare professionals were involved in the study (41.8% nurses, 30.4% doctors, 12.3% laboratory technicians, 15.1% other health professionals): 25 (2.3%), 73 (6.6%) and 35 (3.2%) of these were susceptible to measles, rubella and chicken pox, respectively. The only variable associated with susceptibility of measles was age (p < 0.001). Furthermore, there was evidence of an association between various susceptibilities, particularly between measles and chickenpox (OR: 4.38). Conclusion: this study showed that even if the majority of our healthcare professionals are immunized for MRV, it is necessary not to underestimate the seronegativity of non-immune ones. All health professionals should be vaccinated to ensure safety for patients, especially the weakest.